2010
DOI: 10.1021/ja909752r
|View full text |Cite
|
Sign up to set email alerts
|

NMR Structural and Dynamical Investigation of the Isolated Voltage-Sensing Domain of the Potassium Channel KvAP: Implications for Voltage Gating

Abstract: The structure and dynamics of the isolated voltage-sensing domain (VSD) of the archaeal potassium channel KvAP was studied by high-resolution NMR. The almost complete backbone resonance assignment and partial side-chain assignment of the (2)H,(13)C,(15)N-labeled VSD were obtained for the protein domain solubilized in DPC/LDAO (2:1) mixed micelles. Secondary and tertiary structures of the VSD were characterized using secondary chemical shifts and NOE contacts. These data indicate that the spatial structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 58 publications
7
63
0
Order By: Relevance
“…Included in this collection are integral membrane proteins, such as G-protein coupled receptors (GPCRs) (3035), ion channels (3639), transporters (4045), pores and toxins (46, 47), receptors (4851), cytochrome c oxidase (52); each incorporated into Nanodiscs with precisely controlled compositions. A pictorial "Rogues Gallery" of these embedded proteins is represented in Figure 2.…”
Section: Nanodiscs For Analysis Of Lipid-protein Interactionsmentioning
confidence: 99%
“…Included in this collection are integral membrane proteins, such as G-protein coupled receptors (GPCRs) (3035), ion channels (3639), transporters (4045), pores and toxins (46, 47), receptors (4851), cytochrome c oxidase (52); each incorporated into Nanodiscs with precisely controlled compositions. A pictorial "Rogues Gallery" of these embedded proteins is represented in Figure 2.…”
Section: Nanodiscs For Analysis Of Lipid-protein Interactionsmentioning
confidence: 99%
“…Detergent micelles can retain the proper tertiary structure of some MPs [4][5][6][7] and have relatively small size to provide the NMR spectra with narrow lines; detergents are cheap and some of them are commercially available in a perdeuterated form. On the other hand, micelles have spherical shape and do not contain any patch of a planar lipid bilayer, which can severely affect the spatial structure of MPs, especially of those, containing juxtamembrane regions that tend to interact with the membrane surface 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The first had the VSD solubilized in DPC/LDAO mixed micelles (50 kDa complex at 42 C) (Shenkarev et al 2010a) and provided structural information that matched well with the crystal structure of the isolated VSD in n-octyl-b-D-glucoside (Jiang et al 2003), which has four transmembrane a-helical segments (S1-S4); it was concluded that this NMR structure of the VSD is in a conformation that corresponds to the open-state of the KvAP channel. The second study determined the structure of the VSD in D7PC (1,2-diheptanoyl-sn-glycero-3-phosphocholine) micelles (50-60 kDa complex at 45 C) (Butterwick and MacKinnon 2010) ( Figure 11C) and was generally in overall agreement with the earlier study and with the crystal structure of the isolated VSD.…”
Section: Voltage-sensor Domain Of the Potassium Channel Kvapmentioning
confidence: 83%